2022
DOI: 10.1002/hsr2.671
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of authorized drugs for treating Covid‐19 patients

Abstract: Background and Aims Vaccines are the first line of defense against coronavirus disease 2019 (Covid‐19). However, the antiviral drugs provide a new tool to fight the Covid‐19 pandemic. Here we aimed for a comparative evaluation of authorized drugs for treating Covid‐19 patients. Methods We searched in PubMed and Google Scholar using keywords and terms such as Covid, SARS‐CoV‐2, Coronavirus disease 2019, therapeutic management, hospitalized Covid‐19 patients, Covid‐19 tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 65 publications
0
42
0
Order By: Relevance
“…There is definite evidence that COVID‐19 vaccination reduces the infection rate and disease complications. 30 Studies have shown that hospitalization rate, COVID‐19 complications, and mortality rate were lower among the vaccinated population. In South Africa, much lower deaths and hospitalizations occurred in the fifth wave due to BA.4 and BA.5 subvariants.…”
Section: Covid‐19 Vaccines and Antiviral Agents Against Emerging Vari...mentioning
confidence: 99%
See 1 more Smart Citation
“…There is definite evidence that COVID‐19 vaccination reduces the infection rate and disease complications. 30 Studies have shown that hospitalization rate, COVID‐19 complications, and mortality rate were lower among the vaccinated population. In South Africa, much lower deaths and hospitalizations occurred in the fifth wave due to BA.4 and BA.5 subvariants.…”
Section: Covid‐19 Vaccines and Antiviral Agents Against Emerging Vari...mentioning
confidence: 99%
“…2 The role of the COVID‐19 vaccines is vital to curb the prevalence and mortality. 30 , 31 However, corona antibodies last 6–9 months in the human body. There is definite evidence that COVID‐19 vaccination reduces the infection rate and disease complications.…”
Section: Covid‐19 Vaccines and Antiviral Agents Against Emerging Vari...mentioning
confidence: 99%
“… 17 In an already COVID-19-weary and inflicted society, this new VOC Omicron sparked a new debate about vaccine effectiveness and the current booster campaign. 18 , 19 The distinguishing characteristic of Omicron is the prime immunogenic target of antibodies triggered by immunization or through natural infections, which can hold an astonishingly huge number of genetic alterations (more than 50), of which nearly 30 mutations are on the spike (S) membrane protein; mostly like to aggregate around the site of receptor binding motif; the consensus sequence of this variant has 44 amino acid changes, deletion of 6 amino acids, and insertion of one amino acid when compared to the reference strain of SARS-CoV-2. 20 The presence of a mutation at other sites such as the receptor-binding domain (RBD) and N-terminal domain might induce a neutralizing response on the antibodies.…”
Section: Introductionmentioning
confidence: 99%
“…SARS-CoV-2 infection was first reported in China in December 2019, and was later classified as pandemic by the World Health Organization (WHO) in March 2020 [ 2 ]. The disease spread to about 218 countries and has resulted in over 6.5 million deaths as of 16 September 2022 [ 3 , 4 , 5 ]. SARS-CoV-2 is a 30 kbp RNA virus that encodes four structural proteins and sixteen non-structural proteins [ 6 ].…”
Section: Introductionmentioning
confidence: 99%